An Empirical Investigation of Users' Assessment of XAI Explanations: Identifying the Sweet-Spot of Explanation Complexity - Liedeker, Felix; Düsing, Christoph; Nieveler, Marcel; Cimiano, Philipp
While the importance of explainable artificial intelligence in high-stakes decision-making is widely recognized in existing literature, empirical studies assessing users' perceived value of explanations are scarce. In this paper, we aim to address this shortcoming by conducting an empirical study focused on measuring the perceived value of the following types of explanations: plain explanations based on feature attribution, counterfactual explanations and complex counterfactual explanations. We measure an explanation's value using five dimensions: perceived accuracy, understandability, plausibility, sufficiency of detail, and user satisfaction. Our findings indicate a sweet spot of explanation complexity, with both dimensional and structural complexity positively impacting the perceived value up to a certain threshold.
Keywords: XAI; Explanation Complexity; User Perception

Verantwortung - Höper, Lukas; Schulte, Carsten; Benzmüller, Christoph (Künstliche Intelligenz für Lehrkräfte)

A conductivity-based flow imaging sensor for the investigation of liquid flow dynamics in stationary and moving separation columns packed with Mellapak 250Y - Mamedov, Tural; Ehlert, Thomas; Schleicher, Eckhard; Dias, Felipe D. A.; Schubert, Markus; Kenig, Eugeny Y.; Hampel, Uwe

Critically 3-frustrated signed graphs - Cappello, Chiara; Naserasr, Reza; Steffen, Eckhard; Wang, Zhouningxin (Discrete Mathematics)

Curvature and stability of quasi-geostrophic motion - Suri, Ali (Journal of Geometry and Physics)

Conjugate points along spherical harmonics - Suri, Ali (Journal of Geometry and Physics)

L^1-regularity of strong ILB-Lie groups - Glöckner, Helge; Suri, Ali

Reasoning in Rough Description Logics with Multiple Indiscernibility Relations - Peñaloza, Rafael; Turhan, Anni-Yasmin (Rules and Reasoning - Eighth International Joint Conference, RuleML+RR 2024, Proceedings)

On German Comics Traditions: An Explorative Approach to Digital Comics Historiography - Giesa, Felix; Hartel, Rita; Dunst, Alexander (Comics | Histories)

Klopstock? Oder: wie ein Autorleben erzählt wird (seit fast 300 Jahren) - Elit, Stefan

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

Experimental determination of liquid-side mass transfer coefficients in sandwich packings in the preloading zone and above the loading point - Franke, Patrick; Devasthali, Oorv; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y.

Evaluation of Digital Competencies - Development of an Instrument for Vocational Teacher Training - Sänger, Niklas (International Journal of Vocational Education Studies)
Approaches to modeling and evaluating teachers’ digital competencies are often based on the TPACK model. However, in-depth analyses of the conceptualization of the model show that the specificities of the so-called dual subject matter of vocational education are not sufficiently represented. This article provides insights into the development and testing of an instrument for teachers’ self-assessment of digital competencies in vocational education.The instrument is based on the structure of TPACK but is adapted in various ways to reflect the specificities of vocational education. The aim of this article is to transfer a conceptual extension oft he TPACK model into an initial instrument and to analyze it as part of an initial exploration.
Keywords: Digital Competencies; Dual Subject Matter; Evaluation; TPACK; Vocational Teacher Training

Optimizing Communication for Latency Sensitive HPC Applications on up to 48 FPGAs Using ACCL - Meyer, Marius; Kenter, Tobias; Petrica, Lucian; O’Brien, Kenneth; Blott, Michaela; Plessl, Christian (Lecture Notes in Computer Science)
Abstract Most FPGA boards in the HPC domain are well-suited for parallel scaling because of the direct integration of versatile and high-throughput network ports. However, the utilization of their network capabilities is often challenging and error-prone because the whole network stack and communication patterns have to be implemented and managed on the FPGAs. Also, this approach conceptually involves a trade-off between the performance potential of improved communication and the impact of resource consumption for communication infrastructure, since the utilized resources on the FPGAs could otherwise be used for computations. In this work, we investigate this trade-off, firstly, by using synthetic benchmarks to evaluate the different configuration options of the communication framework ACCL and their impact on communication latency and throughput. Finally, we use our findings to implement a shallow water simulation whose scalability heavily depends on low-latency communication. With a suitable configuration of ACCL, good scaling behavior can be shown to all 48 FPGAs installed in the system. Overall, the results show that the availability of inter-FPGA communication frameworks as well as the configurability of framework and network stack are crucial to achieve the best application performance with low latency communication.

Optimal Alignment of Temporal Knowledge Bases (Extended Abstract) - Gil, Oliver Fernández; Patrizi, Fabio; Perelli, Giuseppe; Turhan, Anni-Yasmin (Proceedings of the 37th International Workshop on Description Logics (DL 2024), Bergen, Norway, June 18-21, 2024)

StencilStream: A SYCL-based Stencil Simulation Framework Targeting FPGAs - Opdenhövel, Jan-Oliver; Alt, Christoph; Plessl, Christian; Kenter, Tobias (2024 34th International Conference on Field-Programmable Logic and Applications (FPL))

HiHiSpMV: Sparse Matrix Vector Multiplication with Hierarchical Row Reductions on FPGAs with High Bandwidth Memory - Tareen, Abdul Rehman; Meyer, Marius; Plessl, Christian; Kenter, Tobias (2024 IEEE 32nd Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))

„...und warum soll das relevant sein?" Kontroverse Deutungen und Relevanzzuschreibungen zur „48er-Revolution" in Schulbüchern der Jahre 1942 bis 2021 - Grauthoff, Fabian; Meyer-Hamme, Johannes; Imoullas, Mohamed Nassim (Geschichte Lernen)

SERI: High-Throughput Streaming Acceleration of Electron Repulsion Integral Computation in Quantum Chemistry using HBM-based FPGAs - Stachura, Philip; Li, Guanyu; Wu, Xin; Plessl, Christian; Fang, Zhenman (2024 34th International Conference on Field-Programmable Logic and Applications (FPL))
The computation of electron repulsion integrals (ERIs) is a key component for quantum chemical methods. The intensive computation and bandwidth demand for ERI evaluation presents a significant challenge for quantum-mechanics-based atomistic simulations with hybrid density functional theory: due to the tens of trillions of ERI computations in each time step, practical applications are usually limited to thousands of atoms. In this work, we propose SERI, a high-throughput streaming accelerator for ERI computation on HBM-based FPGAs. In contrast to prior buffer-based designs, SERI proposes a novel streaming architecture to address the on-chip buffer limitation and the floorplanning challenge, and leverages the high-bandwidth memory to overcome the bandwidth bottleneck in prior designs. Moreover, to meet the varying computation, bandwidth, and floorplanning requirements between the 55 canonical quartet classes in ERI calculation, we design an automation tool, together with an accurate performance model, to automatically customize the architecture and floorplanning strategy for each canonical quartet class to maximize their throughput. Our performance evaluation on the AMD/Xilinx Alveo U280 FPGA board shows that, SERI achieves an average speedup of 9.80 x over the previous best-performing FPGA design, a 3.21x speedup over a 64-core AMD EPYC 7713 CPU, and a 15.64x speedup over an Nvidia A40 GPU. It reaches a peak throughput of 23.8 GERIS ($10^9$ ERIs per second) on one Alveo U280 FPGA. SERI will be released soon at https://github.com/SFU-HiAccel/SERI.

Kulturelle Teilhabe und innovative Preiskonzepte. Einblicke in ein interdisziplinäres Forschungsprojekt - Flath, Beate; Kundisch, Dennis; Wünderlich, Nancy V. (neues museum)